2022
DOI: 10.1055/a-1970-5528
|View full text |Cite
|
Sign up to set email alerts
|

A novel through-the-scope helix tack-and-suture device for mucosal defect closure following colorectal endoscopic submucosal dissection: a multicenter study

Abstract: Background: Complete closure of large mucosal defects following colorectal ESD with through-the-scope clips (TTSC) is oftentimes not possible. We aimed to report an early experience of using a novel through-the-scope suturing system (TTSS) for closing large mucosal defects after colorectal ESD. Methods: We performed a retrospective, multi-center cohort study of consecutive patients who underwent attempted prophylactic defect closure using TTSS after colorectal ESD. The primary outcome was technical success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The effect on CSDB of new topical agents and closing systems is not supported by a high level of evidence [25,26,27,28]. Our results will help the design of a randomized trial investigating the efficacy of these new devices, one that enrolls patients at high risk of CSDB.…”
Section: What Is the Potential Impact Of Such A Prediction Model?mentioning
confidence: 87%
“…The effect on CSDB of new topical agents and closing systems is not supported by a high level of evidence [25,26,27,28]. Our results will help the design of a randomized trial investigating the efficacy of these new devices, one that enrolls patients at high risk of CSDB.…”
Section: What Is the Potential Impact Of Such A Prediction Model?mentioning
confidence: 87%
“…38,39 After defect closure with TTS suturing, delayed bleeding after colonic ESD and EMR were reported in 1.2% and 3.2%, respectively. 38,39 TTS suturing has also been shown to be effective for mucosal incision closure after esophageal POEM and G-POEM. 35,40 Furthermore, preliminary data from our group suggests that TTS suturing may be associated with less procedure time and similar closure rates when compared with the Overstitch for mucosotomy closure during G-POEM.…”
Section: Current Datamentioning
confidence: 99%
“…Farha et al reported the use of a novel through-the-scope (TTS) helix tack-and-suture device for the closure of large mucosal defects after colorectal endoscopic submucosal dissection (ESD; median lesion size 30 mm, interquartile range [IQR] 25–40 mm) 1 . Technical success was achieved in 92.7 % of patients, with a median closure time of 10 minutes (IQR 6.3–17.3 minutes).…”
mentioning
confidence: 99%